Vaccination with the polymorphic membrane protein A reduces Chlamydia muridarum induced genital tract pathology - Müller, Tina; Albrecht, Simone; Miethke, Thomas (Vaccine, 2017)
Chlamydia trachomatis serovars D-K are one of the most frequent causes of sexually transmitted infections of the female genital tract, with possible complications such as hydrosalpinx, pelvic inflammatory disease, extra-uterine gravidity or infertility. We used the murine genital tract infection model with C. muridarum for vaccination studies and found that more than 70% of the infected mice suffered from uterus dilatations and/or hydrosalpinx. Systemic consequences of the vaginal infection were apparent by splenomegaly ten to fifteen days post infection. While cultivable microorganisms were detectable for the first 23days post infection, the first lesions of the genital tract developed at day 15, however, many lesions occurred later in the absence of cultivable bacteria. Lesions were not accompanied by pro-inflammatory cytokines such as IFNɣ, TNF and IL-6, since these cytokines were almost undetectable in the genital tract 43days post infection. To prevent genital tract lesions, we vaccinated mice with the polymorphic membrane protein (Pmp) A in combination with CpG-ODN 1826 as adjuvant. The vaccine lowered the chlamydial burden and the differences were significant at day 10 post infection but not later. More importantly the vaccine decreased the rate and severity of genital tract lesions. Interestingly, control vaccination with the protein ovalbumin plus CpG-ODN 1826 enhanced significantly the severity but not the rate of pathologic lesions, which was presumably caused by the activation of innate immune responses by the adjuvant in the absence of a C. muridarum-specific adaptive immune response. In summary, vaccination with recombinant PmpA plus CpG-ODN 1826 significantly reduced C. muridarum-induced tissue damage, however, CpG-ODN 1826 may aggravate C. muridarum-induced tissue injuries in the absence of a protective antigen.